2005
DOI: 10.1136/sti.2005.014621
|View full text |Cite
|
Sign up to set email alerts
|

Factors affecting vaginal pH levels among female adolescents attending genitourinary medicine clinics

Abstract: Objectives: Vaginal pH is related to hormonal status, and adolescents experience disturbed hormonal patterns following menarche. We assessed hormonal factors and risk of abnormal vaginal pH and bacterial vaginosis (BV) among adolescents attending genitourinary medicine (GUM) clinics. Methods: In a cross sectional study adolescents within 5 years of menarche, (17 years, or with oligoamenorrhoea were recruited. Vaginal pH and BV were assessed and among those not using hormonal contraceptives, estrone-3-glucuroni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
35
1
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(38 citation statements)
references
References 32 publications
1
35
1
1
Order By: Relevance
“…This study investigated changes in vaginal microbiota and pH in never sexually active Ugandan adolescents accounting for different stages of menarche, whereas other studies were limited to sexually active postmenarcheal girls or prepubescent girls (11;13;21;22). Two cross-sectional studies by Brabin et al among postmenarcheal, sexually active adolescents found that younger gynecologic age was associated with increased bacterial vaginosis (BV) but not with higher vaginal pH among sexually active adolescents attending a genitourinary clinic in Manchester, UK (13;21).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This study investigated changes in vaginal microbiota and pH in never sexually active Ugandan adolescents accounting for different stages of menarche, whereas other studies were limited to sexually active postmenarcheal girls or prepubescent girls (11;13;21;22). Two cross-sectional studies by Brabin et al among postmenarcheal, sexually active adolescents found that younger gynecologic age was associated with increased bacterial vaginosis (BV) but not with higher vaginal pH among sexually active adolescents attending a genitourinary clinic in Manchester, UK (13;21).…”
Section: Discussionmentioning
confidence: 99%
“…Two cross-sectional studies by Brabin et al among postmenarcheal, sexually active adolescents found that younger gynecologic age was associated with increased bacterial vaginosis (BV) but not with higher vaginal pH among sexually active adolescents attending a genitourinary clinic in Manchester, UK (13;21). In contrast, Stevens-Simon et al .…”
Section: Discussionmentioning
confidence: 99%
“…Thus, vaginal pH that correlates with pathogenicity results in the formation of bicarbonate-carbonic acid mixtures that are required for C. sordellii spore germination. Hence, altered vaginal pH conditions could result in a better environment for C. sordellii spores to germinate and establish infections (9).…”
Section: Discussionmentioning
confidence: 99%
“…20 A prevalence rate of 34% was reported from adolescents at genitourinary medicine clinics in Manchester, UK. 21 Nonpenetrative intimate sexual contact was associated with detection of G. vaginalis and Atopobium vaginae in a study of vaginal samples from asymptomatic virginal women. 22 A. vaginae has been recognized as part of abnormal vaginal flora, and the metronidazole-resistant characteristics of this anaerobe may contribute to BV recurrence.…”
Section: Introductionmentioning
confidence: 99%